Understanding the relationship between task conflict and construction project performance: uncertainty management perspective - Jia, Jianyao; Gan, Xueqing; Liu, Kangning; Le, Yun (Journal of Civil Engineering and Management, 2024)
Task conflict is prevalent among construction project parties, however, how task conflict affects construction project performance still lacks a comprehensive investigation. Against this background, this study adopts an uncertainty management perspective to conduct an integrative model including both positive and negative mediators as well as one moderator to investigate the link between task conflict and construction project performance. Using 206 samples from the Chinese construction industry, the proposed hypotheses are empirically examined. Results suggest that project commitment (effect size = –0.046) negatively mediates the link between task conflict and project performance, whereas knowledge integration (effect size = 0.053) has a positive mediating effect. What’s more, task reflexivity is found to mitigate the negative effects of task conflict on both project commitment (coefficient of interaction item = 0.12) and knowledge integration (coefficient of interaction item = 0.08). It is also found that task reflexivity changes the direction and strength of the link from task conflict to project performance by both project commitment (from –0.155 to 0.069) and knowledge integration (from –0.049 to 0.052). These findings provide a holistic understanding of the relationship between task conflict and construction project performance, thus contributing to construction project management theoretically and practically.